1998
DOI: 10.1002/j.2161-1882.1998.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of College Retention and GPA: Learning and Study Strategies, Testwiseness, Attitudes, and ACT

Abstract: GFA. Colleges and universities continue to face the issue of student retention. For some researchers (e.g., Braxton & Brier, 1989) and many college counselors and administrators, retention is viewed as a fundamental indicator of student success. Several factors have been shown to be related to college success, such as high school grade point average (GPA), minority status, and study skills (Bean & Metzner, 1985; Carroll, 1988; Guloyan, 1986; Miller, Finley, & Mckinley, 1990; Stoecker, Pascarella, & Wolfe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 11 publications
3
53
0
3
Order By: Relevance
“…Prematriculation measures of expectations such as the one used in the current study rarely ask students to predict whether dramatic changes, specifically negative ones, will occur in the first year of college. Researchers have examined students' abilities to cope with stress, but the questions are typically generic and not specific to the types of situations described above (Gerdes & Mallinckrodt, 1994;Kern et al, 1998). The openended questions in the current study served as a quality check for the Likert-items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prematriculation measures of expectations such as the one used in the current study rarely ask students to predict whether dramatic changes, specifically negative ones, will occur in the first year of college. Researchers have examined students' abilities to cope with stress, but the questions are typically generic and not specific to the types of situations described above (Gerdes & Mallinckrodt, 1994;Kern et al, 1998). The openended questions in the current study served as a quality check for the Likert-items.…”
Section: Discussionmentioning
confidence: 99%
“…Many students are ill-prepared for these changes, partly because college and high school have different standards and expectations (Venezia et al, 2003). Failure to understand the different expectations in the two settings can impact academic motivation and achievement (Kern, Fagley, & Miller, 1998).…”
mentioning
confidence: 99%
“…These include strategies and techniques such as note taking, information processing, selecting main ideas, self-testing, concentration and time management (Proctor, Prevatt, Adams, Hurst, & Petscher, 2006). Numerous studies have demonstrated significant associations between specific study skills and academic success in university students, such as time management (Britton & Tesser, 1991), information processing and self-testing strategies (Kern, Fagley, & Miller, 1998). Researchers have also found that high-achieving students tend to apply study strategies more frequently than their lower achieving counterparts, with frequency of strategy use being positively associated with academic performance (Yip, 2007).…”
Section: Study Skills Attitude and Motivationmentioning
confidence: 99%
“…The association between self-regulation and university performance is well documented in the existing literature. Self-regulated learning strategies such as goal setting (Zimmerman, Bandura, and Martinez-Pons 1992), time management (Britton and Tesser 1991), information processing, and self-testing (Kern, Fagley, and Miller 1998) have been shown to be significantly related to university academic success. There is also an extensive body of evidence which showed that higher and lower academic achievers differ significantly in their abilities to regulate their own learning (Heikkilä and Lonka 2006;Lynch 2006;Zimmerman and Schunk 2008).…”
mentioning
confidence: 99%